Efficacy of Increased Salt and Water Intake on Pediatric Vasovagal Syncope: A Meta-Analysis Based on Global Published Data - Wang, Yaru; Wang, Yuanyuan; Li, Xueying; Du, Junbao; Zhang, Hao; Jin, Hongfang; Liao, Ying (Frontiers in Pediatrics, 2021)
Objective This study was designed to assess the efficacy of increased salt and water intake in the treatment of pediatric vasovagal syncope (VVS) based on a meta-analysis of global data. Methods Following the established inclusion criteria, seven databases, Cochrane Library, EMBASE, PubMed, Web of Science, VIP, Wanfang, and China National Knowledge Infrastructure (CNKI), were searched using specific terms. The Cochrane Bias risk assessment tool was used as a quality assessment tool of the included studies, and publication bias was assessed by funnel plots. Review Manager 5.4 software was used to analyze the efficacy of the included studies, taking the negative rate of the head-up tilt test (HUTT) and recurrence rate of syncope or presyncope as therapeutic efficacy evaluations. Results In total, 5 randomized controlled trials (RCTs) were finally obtained, using the negative rate of the HUTT as an efficacy evaluation, while in 4 of the studies, the recurrence rate of syncope or presyncope was also evaluated. A total of 233 children with VVS were included in the salt and water intervention group. The cases in the control group were treated with nonmedicinal conventional therapy. The results revealed that the negative rate of the HUTT in the intervention group (144/233, 61.8%) was higher than that in the control group (48/179, 26.8%), and the difference was significant (P < 0.00001). The recurrence rate of syncope or presyncope in the intervention group (85/195, 43.6%) was lower than that in the control group (86/144, 59.7%), and the difference was significant (P = 0.002). Conclusion The current findings suggest that increased salt and water intake may increase the negative rates of the HUTT and reduce syncope or presyncope recurrence rates in pediatric patients with VVS.